Agricultural and rural development in Indonesia (Westview Press, 1981)
This book provides a broad, interdisciplinary overview of the major facets of Indonesia's contemporary agricultural and rural development, while exploring the macro and micro factors that account for uneven development patterns. In assessing the rate and distribution of economic growth within the rural sector of the Indonesian archipelago.